Association between self-care behaviors and quality of life among elderly minority groups on the border of Thailand - Parichat Ong-Artborirak (2020)
© 2019 Ong-artborirak and Seangpraw. Introduction: Quality of life among the elderly is an important public health issue. However, few studies have examined the health and quality of life among ethnic minority groups. This research aimed to study the association between self-care behaviors and quality of life among the elderly from ethic minority groups living along the borders of Thailand. Methods: Three provinces from the northern part of Thailand, including Tak, Nan, and Phayao, were selected for the area of study. The purposive method was employed to select districts within the province. Simple random sampling was used to select samples. A total number of 810 elderly citizens were recruited from ethnic minority groups as a research sample. The assessment questionnaire WHOQOL-OLD was used for interviewing the elderly. Results: The mean age of the elderly in our sample was 68.3 years, representing ethnic groups of Lua (30.9%), Karens (24.6%), Tai Lue (23.3%), and Tai Hmong (21.2%). The level of self-care behaviors of these elderly was moderate (49.5%), low (45.9%), and high (4.6%). More than half of them exhibited the quality of life at a moderate level (69.1%) and low level (26.5%); only a few demonstrated a high level (4.4%). Linear regression analysis revealed that self-care behaviors were positively significantly related to the quality of life among ethnic groups (p-value<0.001). Other variables such as age, ethnic group, education, incurrent disease, and smoking were associated with quality of life among the elderly (p-value<0.05). Conclusion: Health promotion to improve health and self-care behaviors among the elderly living along the borders of Thailand should be encouraged through the culture, tradition, and beliefs of particular ethnic groups. Proactive health services and health awareness should be promoted by health agencies and related organizations in order to improve the health, well-being, and quality of life among the elderly people from ethnic minority groups.